Practice change‐savvy leadership to guide your institution into the future. Issue 6 (August 2016) - Fullan, Michael; Scott, Geoff
Abstract : We will need leaders at all levels of the university who can engage in combining analytical and emotional knowledge in the service of morally robust reform.